Controllable Charge Transfer by Ferroelectric Polarization Mediated Triboelectricity. (19th February 2016) - Lee, Keun Young; Kim, Sung Kyun; Lee, Ju‐Hyuck; Seol, Daehee; Gupta, Manoj Kumar; Kim, Yunseok; Kim, Sang‐Woo
Abstract : Next‐generation memory and energy harvesting devices require a higher output performance for charging lectric devices. Generally, it is very limited to control charge transfer through triboelectricity in triboelectric materials. Here, using ferroelectric polarization, it is found that both the amount and direction of charge transfer in triboelectric materials can be controlled. The ferroelectric‐dependent triboelectricity in a ferroelectric co‐polymer film is explored using atomic force microscopy (AFM). Ferroelectric surfaces are rubbed with the AFM tip after poling with positive and negative bias voltages to achieve a triboelectric effect. The surface potential of the positively (negatively) poled area becomes smaller (larger) after rubbing the film surface with the AFM tip. Furthermore, the power output from the triboelectric nanogenerator is dependent on the ferroelectric polarization state. The results indicate that the amount and direction of the charge transfer in triboelectricity can be controlled by the ferroelectric polarization state. Abstract : Modulation of the triboelectricity in ferroelectric material using atomic force microscopy is reported. The surface potential of the positively (negatively) poled area becomes more negative (positive) after rubbing due to the triboelectric effect. The results indicate that the amount and direction of the charge transfer can be controlled by the ferroelectric polarization state.